DIKSI DALAM WACANA IKLAN BERBAHASA INDONESIA Satu Kajian Sosiopragmatik - Tri Sulistyaningtyas (Fakultas Seni Rupa dan Desain ITB, 2008)
The language used in the advertisements of both printed and electronic mass media is often unsuitable with the grammatical rules of Bahasa Indonesia. Due to the ineffective use of Bahasa Indonesia, the intended message conveyed is not accomplished. The facts show that the advertisements are expressed in simple, contextual, and familiar language to the targeted audience. This condition concerns many people. One of the reasons for the advertisements expressed in such a way is because applying the SPOK rule and effective sentences will result in long and unattractive wording. In every advertisement, a catcher